(untitled) - Nguyễn, Thị Quỳnh Hoa (Can Tho, 2016)
This study aims at investigating into cultural obstacles in speaking English, that is students' difficulties and teachers' suggestions
Keywords: Tiếng Anh,English languages; dạy và học,Study and teaching